2012
DOI: 10.2135/cropsci2011.11.0618
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for Energy‐related Traits in a Sweet × Grain Sorghum [Sorghum bicolor (L.) Moench] Mapping Population

Abstract: To meet anticipated markets for sweet sorghum [Sorghum bicolor (L.) Moench] production, the development of sweet sorghum hybrids is underway. As this development is in its infancy, genetic markers will be very useful to define the genetic basis of sugar yield components and reduce the time required to deliver new hybrids to market. The purpose of this research was to characterize genetic components that influence sweet sorghum productivity and agronomics. A grain x sweet sorghum mapping population was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
38
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 31 publications
15
38
2
Order By: Relevance
“…Photoinsensitive genotypes are preferred in breeding schemes since flowering in these materials occurs independently of day length; therefore, these ideotypes can and are used in breeding programs across several distinct environments. Significant genotypic variability was also observed in rather distinct populations consisting of various photoinsensitive and sensitive genotypes and environments [4,8,15,19,26,29,[36][37][38][39], demonstrating that improvement of these traits through genetic manipulation, especially by intercrossing photoinsensitive lines, is feasible in sorghum. Repeatability estimates were moderate to high for all traits, indicating that the phenotyping techniques employed in this study were relatively consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoinsensitive genotypes are preferred in breeding schemes since flowering in these materials occurs independently of day length; therefore, these ideotypes can and are used in breeding programs across several distinct environments. Significant genotypic variability was also observed in rather distinct populations consisting of various photoinsensitive and sensitive genotypes and environments [4,8,15,19,26,29,[36][37][38][39], demonstrating that improvement of these traits through genetic manipulation, especially by intercrossing photoinsensitive lines, is feasible in sorghum. Repeatability estimates were moderate to high for all traits, indicating that the phenotyping techniques employed in this study were relatively consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Gravois et al [27] demonstrated in sugarcane that stalk volume had the greatest influence on stalk weight, followed by negative effects of stalk pithiness and tube formation (stalk's hollow core). At the genetic level, different studies have suggested a pleiotropic role of the genetic determinants controlling multiple stalk-related traits on sorghum juice and sugar yields [15,19,28,29]. However, these and previous studies have not assessed the use of these and other stalk-related traits to predict juice yield.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally 168 QTL for height were also projected onto the consensus genetic linkage map, and included 101 QTL from 15 studies previously detailed in [22] and an additional 67 QTL from 7 more recent studies [28,67-72] (Additional file 3: Table S9). Similarly, 157 QTL for maturity were projected onto the consensus genetic linkage map, and included 62 QTL from 12 studies previously detailed in [20] and an additional 95 QTL from 8 more recent studies [28,59,67,68,70-73] (Additional file 3: Table S9). The QTL for all three traits identified in the three separate mapping populations in the current study were also projected onto the sorghum consensus map, based on the physical locations of the flanking markers, to facilitate comparisons across populations, studies and traits.…”
Section: Methodsmentioning
confidence: 99%
“…A QTL for heading date on the linkage group that aligns with Sb03 was also identified by Gifford et al, (2015) on the same position at the end of the chromosome arm (position 6 -9 cM) as HD2 in this study. In addition, a QTL for heading date was consistently reported in sorghum on the end of the chromosome arm of Sb06 Felderhoff et al, 2012;Zou et al, 2012), which is in accordance with HD3 found in this study.…”
Section: Comparative Analysis Of Qtls In Miscanthus and Sorghumsupporting
confidence: 91%